A Group Collaboratable Proof of Retrievability Scheme for Cloud Data Storage - Lin, Jyh-Shyan; Liao, Kuo-Hsiung; Hsu, Chao-Hsing (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
Cloud computing and cloud data storage have become important applications on the Internet. An important trend in cloud computing and cloud data storage is group collaboration since it is a great inducement for an entity to use a cloud service, especially for an international enterprise. In this paper we propose a cloud data storage scheme with some protocols to support group collaboration. A group of users can operate on a set of data collaboratively with dynamic data update supported. Every member of the group can access, update and verify the data independently. The verification can also be authorized to a third-party auditor for convenience.